The Dehumanizing Effects of Slavery on the African-American Slaves in Toni Morrison’s Beloved: التأثيرات اللانسانية للعبودية على العبيد الأفرو-أميركيين في رواية (المحبوبة) (مجلة ديالى للبحوث الانسانية, 2022)
Toni Morrison won the Pulitzer Prize for fiction in 1988 upon publishing her novel Beloved. It was adapted in 1988 into a film of the same name starring Oprah Winfrey. In 2006 a New York Times survey of writers and literary critics ranked it as the best work of American fiction of the past 25 years. This research intends to show that Toni Morrison makes the reader become aware of the physical and psychological damage done to the African American people by the brutal inhumanity that constituted American slavery. Because of the painful nature of slavery, most slaves repressed their memories in an attempt to leave behind a horrific past. This repression and